Protective and Performance Effects of Anthocyanin Supplementation: A Review of the Literature - Clearkin, Finn (Auckland University of Technology, 2024)
There has been growing interest from both the general and sporting populations in natural occurring plant extracts and phytochemicals that might elicit physiological and ergogenic effects, such as anthocyanin. Anthocyanins are responsible for the natural pigments in the flowers, leaves, fruits, vegetables and tubers; such as blues, purples, reds and oranges. The main aim of this dissertation is to review the literature in order to determine 1) the protective and potential health benefits of anthocyanins; 2) the effects of anthocyanins on physiological responses, and the primary aim; 3) the impact of anthocyanin intake on physical performance and adaptations during exercise. This dissertation comprised five chapters involving both a narrative and systematic review. The narrative review revealed promising protective effects of anthocyanin with daily dosages <300mg assisting in the reduction in the effects of free radicals, oxidative stress and providing anti-inflammatory cytokines to assist in prevention and risk reduction of different types of non-communicable diseases, cancers and neurological degradation. Anthocyanin research has shown beneficial effects to improve recovery and assist in the reduction of exercise-induced oxidative stress. Anthocyanins have vasodilatory properties that can increase peripheral blood flow, which in addition to reducing damage caused by exercise and non-exercise oxidative stress, can assist in enhancing oxygen delivery, muscle metabolite removal, and substrate utilisation. The systematic literature review was performed using PubMed, Scopus, and SPORTDiscus, revealing 11 studies that examined the effects of anthocyanins on physical performance. The studies on berries, such as blackcurrants, showed promising results within a seven-day supplementation period with daily doses of 105mg providing more evidence than 210mg, and 315mg, dosages. There was a notable improvement in cycling performance and indications of performance-enhancing effects from blueberries and cherries as well. Overall, this dissertation offers valuable insights into the effects of anthocyanin consumption on human health, physiology, and exercise performance.